Intraoperative Use of O-arm in Pediatric Cervical Spine Surgery. Issue 4 (April 2020) - Verhofste, Bram P.; Glotzbecker, Michael P.; Hresko, Michael T.; MacDougall, Robert D.; Birch, Craig M.; O'Neill, Nora P.; Karlin, Lawrence I.; Emans, John B.; Proctor, Mark R.; Hedequist, Daniel J.
Abstract : Introduction: Traditionally, fluoroscopy and postoperative computed tomographic (CT) scans are used to evaluate screw position after pediatric cervical spine fusion. However, noncontained screws detected postoperatively can require revision surgery. Intraoperative O-arm is a 3-dimensional CT imaging technique, which allows intraoperative evaluation of screw position and potentially avoids reoperations because of implant malposition. This study's objective was to evaluate the use of intraoperative O-arm in determining the accuracy of cervical implants placed by a free-hand technique using anatomic landmarks or fluoroscopic guidance in pediatric cervical spine instrumentation. Methods: A single-center retrospective study of consecutive examinations of children treated with cervical spine instrumentation and intraoperative O-arm from 2014 to 2018 was performed. In total, 44 cases (41 children, 44% men) with a mean age of 11.9 years (range, 2.1 to 23.5 y) were identified. Instability (n=16, 36%) and deformity (n=10, 23%) were the most frequent indications. Primary outcomes were screw revision rate, neurovascular complications caused by noncontained screws, and radiation exposure. Results: A total of 272 screws were inserted (60 occipital and 212 cervical screws). All screws were evaluated on fluoroscopy as appropriately placed. Four screws (1.5%) in 4 cases (9%) were noncontained on O-arm imaging and required intraoperative revision. A mean of 7.7 levels (range, 5 to 13) were scanned. The mean CT dose index and dose-length product were 15.2±6.87 mGy and 212.3±120.48 mGy×cm. Mean effective dose was 1.57±0.818 mSv. There was no association between screw location and noncontainment ( P =0.129). No vertebral artery injuries, dural injuries, or neurologic deficits were related to the 4 revised screws. Conclusions: Intraoperative non-navigated O-arm is a safe and efficient method to evaluate screw position in pediatric patients undergoing cervical spine instrumentation. Noncontained screws were detected in 9% of cases (n=4). O-arm delivers low radiation doses, allows for intraoperative screw revision, and negates the need for postoperative CT scans after confirmation of optimal implant position. Level of Evidence: Level IV. Abstract : Supplemental Digital Content is available in the text.